2019
DOI: 10.1080/21691401.2019.1615932
|View full text |Cite
|
Sign up to set email alerts
|

Development of R 8 modified epirubicin–dihydroartemisinin liposomes for treatment of non-small-cell lung cancer

Abstract: Presently, there are no few anticancer drugs that have been used clinically due to their poor targeting ability, short half-life period, non-selective distributions, generation of vasculogenic mimicry (VM) channels, high metastasis, and high recurrence rate. This study aimed to explore the effects of R 8 modified epirubicin-dihydroartemisinin liposomes that could target non-small-cell lung cancer (NSCLC) cells, destroy VM channels, inhibit tumor metastasis, and explain the possible underlying mechanism. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 39 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…R8-modified epirubicin-dihydroartemisinin liposomes have been reported to suppress VM through regulating the levels of VE-cad, TGF-β, MMP-2, and HIF-1α in non-small-cell lung cancer. Epirubicin is an anti-tumor drug most [73] commonly applied in the treatment of various cancer types, and dihydroartemisinin is an anti-malarial drug but also has anti-tumor effects [115]. Additionally, ginsenoside Rg3 (Rg3) is a tetracylic triterpenoid saponin that inhibits tumor cell proliferation, adhesion, and tumor angiogenesis.…”
Section: Clinical Significance Of Vm In Cancermentioning
confidence: 99%
“…R8-modified epirubicin-dihydroartemisinin liposomes have been reported to suppress VM through regulating the levels of VE-cad, TGF-β, MMP-2, and HIF-1α in non-small-cell lung cancer. Epirubicin is an anti-tumor drug most [73] commonly applied in the treatment of various cancer types, and dihydroartemisinin is an anti-malarial drug but also has anti-tumor effects [115]. Additionally, ginsenoside Rg3 (Rg3) is a tetracylic triterpenoid saponin that inhibits tumor cell proliferation, adhesion, and tumor angiogenesis.…”
Section: Clinical Significance Of Vm In Cancermentioning
confidence: 99%
“…Recent studies have also reported an anti-proliferative effect of DHA on lung cancer, breast cancer, colon cancer, and cervical cancer cell lines, with minimal cytotoxicity in normal cells (Zhang et al., 2012 ; Wu et al., 2013 ; Lu et al., 2018 ; Liu et al., 2018a ). The anti-cancer effects of DHA are mainly attributed to its inhibition of angiogenesis, induction of cell apoptosis and modulation of tumor-related genes (Dell'Eva et al., 2004 ; Liu et al., 2019 ; Wan et al., 2019 ). At the molecular level, the cleavage of the iron- or heme-mediated peroxide bridge and generation of reactive oxygen species (ROS) is the possible mechanism of DHA toxicity (Sun et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Galunisertib, an anti-tumor TGF-β pathway kinase inhibitor, has been found to effectively inhibit the VM of tumors [214]. Some of these drugs have been obtained from clinical trials, whereas some antitumor drugs are modified from traditional drugs like R 8 modified epirubicin-dihydroartemisinin liposomes [218].…”
Section: Vasculogenic Mimicry Inhibitorsmentioning
confidence: 99%